Effects of plasticizers on the properties of oat starch films - Galdeano, Melícia Cíntia (2009)
Oat starch films were prepared by casting using glycerol, sorbitol, glycerol-sorbitol mixture, urea and sucrose as plasticizers. The effects of these plasticizers on the microstructure, moisture sorption, water vapor permeability (WVP) and mechanical properties were investigated using films stored under a range of relative humidities. The plasticizer type did not affect significantly (p ≤ 0.05) the equilibrium moisture content of films, except at 90% relative humidity (RH). Films without plasticizer adsorbed less water and showed higher WVP than plasticized ones, indicating the antiplasticizing effect observed in this work. In general, a decrease in stress at break and Young's modulus and an increase in strain at break were observed when RH increased in all film formulations. Films without plasticizer showed higher stress at break values than the plasticized ones and presented stable strain at break under a range of RH. Sucrose films were the most fragile at low RH while glycerol films were the most hygroscopic.